Course of the pregnancy in women with connective tissue disorders - Ilina I.Yu; A.A. Chikisheva (LCC «Medicine-Inform», 2020)
I.Yu. Il'ina, A.A. Chikisheva Pirogov Russian National Research Medical University, Moscow, Russian Federation This paper discusses connective tissue disorders (CTD), in particular, undifferentiated connective tissue disease (UCTD) whose importance is accounted for by a high prevalence of this condition. Generalized connective tissue damage that involves reproductive system significantly affects the course of pregnancy and delivery. The complications of pregnancy, delivery, and postpartum period in women with UCTD which often require surgical procedures (i.e., amniotomy, episiotomy, perineotomy, C-section etc.) are described. The paper highlights the role of magnesium which is of crucial importance for the complex biosynthesis of extracellular matrix during connective tissue formation and fibroblast morphological functional status. The tests for connective tissue metabolic disorders (blood oxyproline and fibronectin, urine pyrilinks-D and glycosaminoglycans etc.) are addressed. Considering the lack of the reliable diagnostic (biochemical and genetic) criteria for UCTD, the authors advo cate the need for a complex examination using anamnestic data and the results of clinical, instrumental, and laboratory tests. Keywords: connective tissue disorders, hemostasis, complications of pregnancy and delivery, magnesium deficiency, endothelial dysfunction, markers of collagen degradation, genital prolapse. For citation: Il'ina I.Yu., Chikisheva A.A. Course of the pregnancy in women with connective tissue disorders. Russian Journal of Woman and Child Health. 2020;3(3):182-188. DOI: 10.32364/2618-8430-2020-3-3-182-188.